Comparison of virtual visit versus traditional clinic for management of varicose veins. (January 2020) - Lin, Judith C; Mclaughlin, Dylan; Zurawski, Dana; Kennedy, Nicole; Kabbani, Loay
Introduction: The objective of this study is to compare the clinical outcomes of patients with varicose veins managed in the telemedicine clinic and traditional clinic. Methods: Retrospective analysis of all vein procedures in the institutional Vascular Quality Initiative Varicose Vein Registry (VQI VVR) was performed from January 2015 to August 2017. Patients were divided into two groups: Telemedicine versus Traditional Clinic. Comparison data included patient demographics, past medical history, clinical outcomes, patient-reported outcomes and postoperative complications. Statistical testing included chi-square test for categorical variables and student t -test for continuous variables using the SPSS statistical software. Results: A total of 1034 varicose vein procedures were performed during the 31-month study period. There were 75 virtual encounters in the Telemedicine Clinic (Group A) and 959 face-to-face encounters in the Traditional Clinic (Group B). Most of the demographics characteristics were clinically similar in both groups. Comparing Group A and Group B, there were no differences in age, sex, race and body mass index. Early 3-month follow up was 100% in Group A and 90.7% in Group B. Both groups had low complication rates of haematoma (1.3% vs 0.3%, p  = 0.884), paraesthesia (1.3% vs 0.6%, p  = 0.767) and recanalisation (1.3% vs 4.0%, p  = 0.383) during the early follow up period. Discussion: Synchronous virtual visits for patient care are feasible for the management of chronic venous disease. Patients with varicose veins who choose to undergo telemedicine evaluations have similar pre-operative demographics, clinical classification and patient outcomes.